Conversation Analysis Between Health Workers and HIV/AIDS Positive Patients at Soko Community Health Center, Indonesia - Anissa Feby Widya Prawesti (Universitas Nahdlatul Ulama Surabaya, 2025)
Through interpersonal communication, health workers can explain and communicate directly with patients and can see the patient's level of understanding of the disease. In the HIV screening test process, after the patient has completed all stages of the examination, patients who test positive for HIV/AIDS will be transferred to the infectious disease polyclinic to convey the results of the examination, and health workers will explore information related to the cause or history of the patient's healthy lifestyle behavior. The research subjects are informants or sources who are related to those being studied in order to obtain information related to research data. The subjects or informants of this study are patients who are confirmed positive for HIV/AIDS. In a condition when someone is diagnosed with HIV/AIDS, in this case the patient tends to be passive and still tries to accept that the diagnosis is positive for HIV/AIDS. However, health workers approach by communicating and showing an assertive attitude, empathy, providing motivation and complete explanation. With health workers approaching in this way, it turns out that they are able to make patients more open and accept the situation. This also shows a level of compliance with HIV/AIDS care.